Determination of surface defects by using the wavefront scanner - Goloborodko, N.S.; Grygoruk, V.I.; Kurashov, V.N.; Podanchuk, D.V.; Goloborodko, A.A.; Kotov, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The possibility of changes in the polarization state of the laser beam reflected
from inhomogeneity with the refractive index gradient is theoretically shown, which
allows separating the phase shifts related with relief inhomogeneities and local changes
of the surface refractive index. Modification of the wavefront scanner for analyzing the
wavefront of the laser beam reflected from the samples’ surface is considered. The main
idea of the method is to use the focused laser beams with different polarizations for
illuminating separate areas of the surface. The results of detecting test surfaces with
different structures by the wavefront scanner are presented.